Clinical and Cytometric Study of Immune Involvement in a Heterogeneous Cohort of Subjects With RASopathies and mTORopathies - Valencic, Erica; Da Lozzo, Prisca; Tornese, Gianluca; Ghirigato, Elena; Facca, Francesco; Piscianz, Elisa; Faletra, Flavio; Taddio, Andrea; Tommasini, Alberto; Magnolato, Andrea (Frontiers in Pediatrics, 2021)
RASopathies and mTORopathies are groups of genetic syndromes associated with increased activation of the RAS-MAPK or the PI3K-AKT-mTOR pathway, resulting in altered cell proliferation during embryonic and postnatal development. The RAS-MAPK and the PI3K-AKT-mTOR pathways are connected to each other and play a crucial role in adaptive immunity. However, with the exception of APDS, immune function has not been deeply studied in these disorders. We collected clinical and immunophenotypic data of a cohort of patients with RASopathies and mTORopathies. Overall, we enrolled 47 patients (22 females, 25 males, age 2-40 years): 33 with neurofibromatosis type 1, 11 Noonan syndrome and 3 Bannayan-Riley-Ruvalcaba syndrome. 8 patients reported a history of invasive infections requiring hospitalization and intravenous antibiotic therapy. Only 3 patients reported a history of unusual, difficult-to-treat or deep-seated infection. Adenotonsillectomy was performed in 11 patients (24%). However, in most cases (83%) patients’ parents did not perceive their child as more prone to infections than their peers. Lymphocyte subpopulations were analyzed in 37 of the 47 patients (16 female, 21 males, age 1-40 years). Among the studied lymphocyte subsets, the only consistent alteration regarded an increased percentage of immature B cells (recent bone marrow emigrants) in 34 out of 37 (91,9%) patients, and an increased percentage of double negative T cells in 9 patients. In conclusion, although borderline immune abnormalities were present in a significant proportion of subjects and adenotonsillectomy was performed more frequently than expected for the general population, no major immune disturbance was found in this cohort of patients.